Creep strengthening by lath boundaries in 9Cr ferritic heat-resistant steel. (1st February 2016) - Mitsuhara, Masatoshi; Yamasaki, Shigeto; Miake, Masaki; Nakashima, Hideharu; Nishida, Minoru; Kusumoto, Junichi; Kanaya, Akihiro
Abstract: The interactions between dislocations and lath boundaries in Grade 91 steel were observed by an in situ transmission electron microscopy tensile test at 973 K. Dislocations glided slowly and bowed out in a martensite lath interior. The ends of the dislocation were connected to the lath boundaries. In a tempered specimen, the pinning stress caused by the lath boundary was estimated to be >70 MPa with a lath width of 0.4 μm. In crept specimens, lath coarsening reduced the pinning effect.